A numerical framework to predict the fatigue life of lattice structures built by additive manufacturing. (October 2020) - Burr, Alexis; Persenot, Théo; Doutre, Pierre-Thomas; Buffiere, Jean-Yves; Lhuissier, Pierre; Martin, Guilhem; Dendievel, Rémy
Graphical abstract: Highlights: Fatigue failure of lattice structures is gradual, exhibiting a so-called grace period. Fatigue properties of lattices depend on additive manufacturing inherited defects. A cascading failure-based model correctly predicts grace period and fatigue life. Abstract: The fatigue properties of lattice structures produced by S-EBM are investigated. Fatigue failure is shown to be gradual, fostering the concept of grace period, defined as the number of cycles lived by the lattice structure after the failure of the first strut. A numerical framework based on the cascading failure of struts is proposed, relying on a damage accumulation law. Each strut is assigned a radius as well as an S-N curve, which both depend on the manufacturing conditions. Through statistical analyses, we demonstrate that the model can correctly predict the grace period and the fatigue life of experimental specimens.